2005
DOI: 10.1016/j.jsames.2005.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The fossil record of South American short-faced bears (Ursidae, Tremarctinae)

Abstract: The present study includes a review of the geographic and stratigraphic distribution of short-faced bears (Ursidae, Tremarctinae) in South America. In addition, the authors discuss biogeographic hypotheses regarding the origin of South American tremarctines. The Tremarctinae subfamily is distributed exclusively in America, from Alaska to southern Patagonia. Its biochron comprises the temporal lapse between Late Miocene and recent times; the first record of Tremarctinae in North America corresponds to the Hemph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
18

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 10 publications
4
73
0
18
Order By: Relevance
“…Such procedure took into account the occurrence of extinct Quaternary mammals above 50 kg in the Mato Grosso do Sul, Brazilian Intertropical region, São Paulo, Rio Grande do Sul, Uruguay, Mesopotamian region, North central Argentina, South of Bolivia, Paraguay and Pampean region. In Table 1, we present a matrix of presence (1) and absence (0) of taxa in South American paleozoogeographical zones, identified to species level, based on Prado & Alberdi (1999), Bond et al (2001), Alberdi & Prado (2004), Carlini et al (2004), Noriega et al (2004), Zurita et al (2004Zurita et al ( , 2007Zurita et al ( , 2011, Soibelzon et al (2005Soibelzon et al ( , 2012, Salles et al (2006), Pitana & Ribeiro (2007), Scherer et al (2007), Scheffler et al (2010), Pitana (2011), Miño-Boilini (2012, Silva et al (2012), Zurita et al (2012) including the specimens herein identified. The cluster analysis was performed on binary matrix employing the clustering algorithm UPGMA (Average Linkage Clustering; Sokal & Michener, 1958) and the Euclidean similarity index using the software Past 3.14.…”
Section: Methodsmentioning
confidence: 99%
“…Such procedure took into account the occurrence of extinct Quaternary mammals above 50 kg in the Mato Grosso do Sul, Brazilian Intertropical region, São Paulo, Rio Grande do Sul, Uruguay, Mesopotamian region, North central Argentina, South of Bolivia, Paraguay and Pampean region. In Table 1, we present a matrix of presence (1) and absence (0) of taxa in South American paleozoogeographical zones, identified to species level, based on Prado & Alberdi (1999), Bond et al (2001), Alberdi & Prado (2004), Carlini et al (2004), Noriega et al (2004), Zurita et al (2004Zurita et al ( , 2007Zurita et al ( , 2011, Soibelzon et al (2005Soibelzon et al ( , 2012, Salles et al (2006), Pitana & Ribeiro (2007), Scherer et al (2007), Scheffler et al (2010), Pitana (2011), Miño-Boilini (2012, Silva et al (2012), Zurita et al (2012) including the specimens herein identified. The cluster analysis was performed on binary matrix employing the clustering algorithm UPGMA (Average Linkage Clustering; Sokal & Michener, 1958) and the Euclidean similarity index using the software Past 3.14.…”
Section: Methodsmentioning
confidence: 99%
“…The oldest known Arctotherium specimens are giant-sized [3,8,10], suggesting either that their size evolution occurred very rapidly or that fossils from the early stages of Arctotherium evolution have not yet been recorded. Our molecular dating estimates are compatible with both possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…After the Plio-Pleistocene boundary (subsequent to GABI), the top predator guild in the South America Ensenadan ecosystems included seven species: Theriodictis platensis Mercerat, Protocyon scagliorum Kraglievich, P. troglodytes (Lund) and Canis (?) gezi Kraglievich (Canidae: Prevosti, 2007), Smilodon populator, Panthera onca (Linnaeus) and Puma Jardine (Felidae: Soibelzon and Prevosti, 2007), and Arctotherium angustidens (Ursidae, Soibelzon, 2004;Soibelzon et al, 2005) (see Webb, 2006). The fast diversification of carnivore guild possibly led to the evolution of different strategies (e.g., behavioral, physiological, anatomical) in the potential prey (Soibelzon et al, 2009b).…”
Section: Paleoecological Contextmentioning
confidence: 99%